2015
DOI: 10.4238/2015.september.22.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of icariin on the expression of ER, VEGF, and KDR in the endometrial cells of thin endometrium

Abstract: ABSTRACT. We explored the effects of icariin on the expression of estrogen receptor (ER), vascular endothelial growth factor (VEGF), and kinase insert domain receptor (KDR) in the endometrial cells of the thin endometrium. Primary endometrial cells were obtained and divided into a blank control group, a high-, a middle-, and a low-dose icariin groups, as well as an estrogen treatment group to undergo cellular identification by immunocytochemistry. The expression levels of ER, VEGF, and its receptor were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The effect and dosage of PE, estrogen concentration in the body, and functional status of the target organ are all interdependent (Beck et al, 2003). We have previously shown that thin endometria exhibited low expression of ER and VEGF, even though the blood concentration of estrogen in the body remained normal (Le et al, 2015). In this study, VEGF, CD31, and factor VIII were significantly elevated in rats receiving medium and high doses of ICA, which was indicative of neovascularization.…”
Section: Vegf Expressionsupporting
confidence: 48%
“…The effect and dosage of PE, estrogen concentration in the body, and functional status of the target organ are all interdependent (Beck et al, 2003). We have previously shown that thin endometria exhibited low expression of ER and VEGF, even though the blood concentration of estrogen in the body remained normal (Le et al, 2015). In this study, VEGF, CD31, and factor VIII were significantly elevated in rats receiving medium and high doses of ICA, which was indicative of neovascularization.…”
Section: Vegf Expressionsupporting
confidence: 48%
“…The growth and development of the bone cannot be achieved and sustained unless from the nutritional support of blood ( Filipowska et al, 2017 ). The VEGF is the critical pro-angiogenic factor for vascular formation ( Zhang et al, 2013 ; Le et al, 2015 ). Thiram appeared to cause up-regulation of VEGF expression, suggesting that it has proangiogenic activity ( Rath et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that angiogenesis is essential for tendon-bone healing by detecting CD31 and VEGF expression in the tendon-bone junction (19–21) [17]. ICA has also been shown to promote angiogenesis [52,53,54,55]. Chung et al investigated the molecular effect of ICA on angiogenesis and demonstrated that ICA stimulates angiogenesis by activating the MEK/ERK and PI3K/Akt/eNOS-dependent signal pathways in human endothelial cells [52].…”
Section: Discussionmentioning
confidence: 99%
“…Xin et al studied the effect of ICA on diabetic retinopathy in a rat model and found a significantly increased expression of VEGF in the retinal vessels of diabetic rats after treatment by ICA [55]. In 2015, Le et al conducted an in vitro study and demonstrated that the endometrium may be thickened by ICA treatment, by increasing the expression levels of VEGF in endometrial cells [53]. Similarly, in our study, the histological results showed that ICA clearly enhanced angiogenesis, compared with the control group.…”
Section: Discussionmentioning
confidence: 99%